LA RÉTROJECTION DU SUBLIME ET LE PAYSAGE TRANSCENDANTAL DANS LA PHÉNOMÉNOLOGIE NON-SYMBOLIQUE DE MARC RICHIR - Codruţa FURTUNĂ (Studia Universitatis Babeș-Bolyai. Philosophia, 2016)
Retrojection of Sublime and Transcendental Landscape in the Non-Symbolic Phenomenology of Marc Richir. This paper deals with an inquiry of the non-symbolic phenomenology and, more precisely, of the Richirian transcendental landscape considered as a consequence of retrojection of sublime. The landscape questions the use of the three stages of passive synthesis and the transcendental game of qualia in creating a proto-area of phenomenological freedom. To illustrate this transcendental landscape we used for methodological reasons a brief phenomenological analysis of the American Abstract Expressionism represented here by the works of Barnett Newman and Mark Rothko. The issue of the transcendental landscape may resemble to a simulation that reduces itself to a Matrix reality- as authors like Philip Kindred Dick to Nick Bostrom argue.